1981
DOI: 10.1042/cs0600157
|View full text |Cite
|
Sign up to set email alerts
|

Local Regulation of Blood Flow in Subcutaneous Tissue in Patients with Acute Myocardial Infarction

Abstract: 1. Local regulation of subcutaneous blood flow in the forearm was studied in the acute phase of myocardial infarction. Blood flow was measured by the local 133Xe-washout technique. 2. Plasma concentrations of noradrenaline and adrenaline were increased on day 1, suggesting an increase in sympathetic neuronal activity, but gradually returned to normal thereafter. 3. Subcutaneous blood flow on day 1 was far below normal (38%) and steadily increased to reach normal at day 7 after coronary occlusion. The sympathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
2
8
0
Order By: Relevance
“…The absence of the vasoconstrictor response may be due to possible increased sympathetic activity caused by pain and operative stress. This is in analogy with the absence of the vasoconstrictor response during acute myocardial infarction, demonstrated in human subcutaneous forearm tissue [6]. In cat skeletal muscle it has been shown that fl-adrenergic stimulation attenuated the myogenic reactivity to increased transmural pressure [16].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The absence of the vasoconstrictor response may be due to possible increased sympathetic activity caused by pain and operative stress. This is in analogy with the absence of the vasoconstrictor response during acute myocardial infarction, demonstrated in human subcutaneous forearm tissue [6]. In cat skeletal muscle it has been shown that fl-adrenergic stimulation attenuated the myogenic reactivity to increased transmural pressure [16].…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, the hyperaemia after arterial reconstruction was calculated in each individual limb as the ratio between the mean postoperative kheart value and the mean preoperative kheart value [ 1,6]. The local adipose tissue radiation dose was estimated to 1 1 rad and the gonadal dose to 2 mrad [7].…”
Section: Methodsmentioning
confidence: 99%
“…Our results of reduced skin blood flow are in accordance with the only two studies of peripheral blood flow in the acute phase of AMI. Skagen et al [23] measured subcutaneous blood flow with local 133 Xe-washout technique on days 1, 3 and 7 after AMI. Subcutaneous blood flow on day 1 was far below normal, but steadily increased to reach normal at day 7 after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Redistribution of cardiac output is associated with an increase in average peripheral resistance. Peripheral blood flow (calf blood flow [22], and subcutaneous blood flow [23]) normalize in 7 days after uncomplicated AMI, which coincides with normalization of circulating levels of catecholamines. However, the degree and duration of neurohumoral activation appears largely related to the degree of left ventricular dysfunction [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that during the acute phase of myocardial infarction the vascular tone in subcutaneous tissue is increased; further, the local veno-arteriolar reflex [ 1,2] elicited by venous distension is abolished on day 1, and then gradually reappears thereafter [3]. On the other hand centrally neurogenically-mediated vasoconstriction in subcutaneous tissue is unchanged during the whole course of myocardial infarction [4].…”
Section: Introductionmentioning
confidence: 97%